1994
DOI: 10.21273/jashs.119.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intraspecific Resistance Variability in Myrobalan Plum, Peach, and Peach-Almond Rootstock Using 22 Root-knot Nematode Populations

Abstract: Resistance variability was evaluated for five rootstock: three Myrobalan plum (Prunus cerasifera Ehr.) genotypes (P.1079, P.2175, and P.2032) grown from in vitro plantlets, one peach (P. persica (L.) Batsch `GF 305') grown from seeds, and one peach-almond hybrid (P. persica × P. amygdalus Batsch `GF 557') grown from rooted cuttings. Twenty-two root-knot nematode populations from different origins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“… Numbers in brackets refer to the following references: 1, Esmenjaud et al . (); 2, Esmenjaud et al . (); 3, Khallouk et al .…”
Section: Resistance In the Genus Prunusmentioning
confidence: 99%
“… Numbers in brackets refer to the following references: 1, Esmenjaud et al . (); 2, Esmenjaud et al . (); 3, Khallouk et al .…”
Section: Resistance In the Genus Prunusmentioning
confidence: 99%
“…Mi-1 is also being studied with regard to its structure and function in regulating the resistance response (Hwang et al 2000;Hwang and Williamson 2003) and has been shown to bind and hydrolyse ATP (Tameling et al 2002). Unlike Mi-1 (Holtzmann 1965;Dropkin 1969;Roberts et al 1990; Kaloshian et al 1996;Williamson 1998), the expression of resistance by the Ma gene from Myrobalan plum (Prunus cerasifera L.) is not affected by high temperatures (Esmenjaud et al 1996a) and no virulent population overcoming this resistance gene is yet known (Esmenjaud et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Rosa multiflora and P. cerasifera have complementary host ranges. First, R. multiflora is a host for M. hapla, whereas P. cerasifera is not (Esmenjaud et al 1994b). Secondly, R. multiflora is resistant to all mitotic species, whereas P. cerasifera is susceptible to them.…”
Section: Discussionmentioning
confidence: 99%